Transitions across schools and cultures - Karabenick, Stuart A.; Urdan, Timothy C. (Advances in motivation and achievement, 2012)
This volume focuses on the "Transitions" that take place at major points of potential discontinuity in students' developmental trajectories and across contexts at a given time point. The development literature, for example, has examined how children's motivation and achievement are affected by the shift from pre-school to school. And a topic that has received considerable attention in the achievement motivation literature is the transition from elementary to middle school. There is less information about the middle to high school transition. The transition from high school to college or school to work represents another important inflection point. Other transitions concern switching from one culture to another over time (e.g., immigration and acculturation), or at a given time point, such as when students shuttle between a dominant school culture and a minority home culture, or foreign students at colleges and universities who may study and socialize with other students from their home culture as well as those from the host culture.